2013
DOI: 10.3109/00952990.2013.847446
|View full text |Cite
|
Sign up to set email alerts
|

Striatal-insula circuits in cocaine addiction: implications for impulsivity and relapse risk

Abstract: Cocaine addiction, relapse risk and impulsivity were associated with reduced connectivity in putamen-posterior insula/postcentral gyrus circuits implicated in temporal discounting and habitual responding. Findings provide new insight into the neurobiological mechanisms underlying impulsivity and relapse in cocaine addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 68 publications
8
82
2
Order By: Relevance
“…Finally, cocaine-dependent subjects who relapse within 30 days of treatment display reduced connectivity between amygdala subregions and ventromedial and rostral anterior cingulate cortices (McHugh et al, 2014). It is important to note that altered functional connectivity in cocaine users may depend on the duration of abstinence before relapse (Camchong et al, 2011;McHugh et al, 2013) and is associated with cognitive deficits (Motzkin et al, 2014). Similar, and perhaps even greater, effects might occur following chronic use of MDPV.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, cocaine-dependent subjects who relapse within 30 days of treatment display reduced connectivity between amygdala subregions and ventromedial and rostral anterior cingulate cortices (McHugh et al, 2014). It is important to note that altered functional connectivity in cocaine users may depend on the duration of abstinence before relapse (Camchong et al, 2011;McHugh et al, 2013) and is associated with cognitive deficits (Motzkin et al, 2014). Similar, and perhaps even greater, effects might occur following chronic use of MDPV.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the inter-network connectivity involving the insula has been reported to be weaker in cocaine users and related to their impulsivity [16] . The insular-striatal connection also mediates the association between impulsivity and cocaine relapse [17] . Moreover, inter-hemispheric insular FC is associated with addictive disorder [18] .…”
Section: The Insula and Addictionmentioning
confidence: 99%
“…As the loss of control in online gaming is one essential criterion of IGD [4] , high impulsivity could make subjects yield to the rewarding effect of gaming and contribute to the vulnerability of IGD. Further, the impulsivity has been reported to correlate with FC of the insula and nucleus accumbens [17,23] , particularly to the frontal lobe [15] . Thus, we hypothesized that impulsivity may influence the vulnerability of IGD by impacting its neurobiological underpinnings in FC of the insula and nucleus accumbens.…”
Section: Impulsivity and Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, voxelbased morophometry (VBM) studies have shown smaller volumes of the striatum, prefrontal cortex, temporal cortex and insula, in cocaine users compared to controls (Ersche et al, 2011;Franklin et al, 2002;Moreno-López et al, 2012;Weller et al, 2011). These regions, in particular the circuit including the insula and the prefrontal cortex, play an important role in the control over impulsive behaviour in addiction (Bari and Robbins, 2013;Jentsch and Taylor, 1999;McHugh et al, 2013;Noël et al, 2013). Unfortunately, only few VBM studies directly investigated the relation between cortical morphometry and trait impulsivity in cocaine users and controls.…”
Section: Introductionmentioning
confidence: 99%